2019
DOI: 10.1097/pgp.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Protein Expression in Endometrioid Intraepithelial Neoplasia/Atypical Hyperplasia: Should We Screen for Lynch Syndrome in Precancerous Lesions?

Abstract: Screening for Lynch syndrome (LS) is routinely performed in patients with endometrial carcinoma. Currently, no screening recommendations exist for LS in precancerous lesions. The study goal was to determine the incidence of abnormal protein expression in endometrioid intraepithelial neoplasia/atypical hyperplasia (EIN/AH). We analyzed mismatch repair (MMR) protein expression by immunohistochemistry in EIN/AH concurrent with MMR-deficient endometrial carcinomas, and in endometrial biopsy/curettage specimens wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…As expected for a heterozygous germline variant, AF was higher than other somatically acquired mutations and showed little fluctuation (Figure 2A). Thus, the HTS panel was able to detect classifying somatic mutations such as POLE and germline mutations that predispose to endometrial cancer [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected for a heterozygous germline variant, AF was higher than other somatically acquired mutations and showed little fluctuation (Figure 2A). Thus, the HTS panel was able to detect classifying somatic mutations such as POLE and germline mutations that predispose to endometrial cancer [22].…”
Section: Resultsmentioning
confidence: 99%
“…Fixation, sectioning, antigen retrieval, blocking, and secondary detection were performed as previously described [21], with the following antibodies: ARID1A [#12354, rabbit monoclonal antibody (mAb); Cell Signaling Technology, Danvers, MA, USA; 1:200], PTEN (Dako #M326‐7, mouse mAb; Agilent Technologies, Santa Clara, CA, USA; 1:150), p53 (Dako #DO‐7, prediluted; Agilent), and β‐catenin (Dako #IR702, mouse mAb). IHC for four MMR proteins was performed as previously described [22]. Antigen retrieval was performed following the manufacturers' recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…EAH/EIN is the precursor lesion of almost all endometrioid carcinomas and a subset of serous carcinomas [58]. The mutational profile of EAH/EIN and the concurrent EC is highly concordant [18,59–62] in the majority of cases; however, Li et al showed that, in 5 out of 30 EAH/EIC cases with concurrent EEC, the EAH/EIC and EC shared less than 5% of the mutations identified, indicating clonality but with a high degree of divergence [62]. Serous intraepithelial carcinoma (SEIC) is characterized by pre‐existing endometrial glands lined by markedly atypical glandular epithelial cells in the absence of invasive disease.…”
Section: Precursors Of Endometrial Carcinomamentioning
confidence: 99%
“…present in the low‐grade areas, or it can occur later and only be seen in the high‐grade serous component (Figure 2D,E). MMRd : These carcinomas are mostly of endometrioid histotype and there can be co‐existing EAH/EIN as the precursor lesion [60]. There is identical loss of MMR protein(s) in the EAH/EIN as in the associated carcinoma in most but not all cases (Figure 2F).…”
Section: Morphological Features Of the Endometrial Carcinoma Precursomentioning
confidence: 99%
See 1 more Smart Citation